Response of Cyclopia subternata to drought stress – assessment of leaf composition, proteomics and product quality - G.S. Mabizela; M. van der Rijst; M.M. Slabbert; P. Mathabe; M. Muller; D. de Beer; M. Stander; J. Colling; B. Walczak; E. Joubert; C. Bester (South African Journal of Botany, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Unexpected survival of sharptooth catfish Clarias gariepinus (Burchell 1822) during acute rotenone toxicity trials will complicate management of invasions - Martine S. Jordaan; Tatenda Dalu; Ryan J. Wasserman; Etienne Slabbert; Olaf L. F. Weyl (Biological Invasions, 2017)

Microbial diversity and community structure in Fynbos soil - ETIENNE SLABBERT; RAPHAEL Y. KONGOR; KAREN J. ESLER; KARIN JACOBS (Molecular Ecology, 2010)
The Fynbos biome in South Africa is renowned for its high plant diversity and the conservation of this area is particularly important for the region. This is especially true in the case of endangered vegetation types on the lowlands such as Sand Fynbos, of which only small fragments remain. The question is thus whether the diversity of the above‐ground flora is mirrored in the below‐ground microbial communities. In order to determine the relationship of the above‐ and below‐ground communities, the soil community composition of both fungal and bacterial groups in Sand Fynbos was characterized over space and time. A molecular approach was used based on the isolation of total soil genomic DNA and automated ribosomal intergenic spacer analysis of bacterial and fungal communities. Soil from four different sites was compared to resolve the microbial diversity of eubacterial and fungal groups on a local (alpha diversity) scale as well as a landscape scale (beta diversity). The community structures from different sites were compared and found to exhibit strong spatial patterns which remained stable over time. The plant community data were compared with the fungal and the bacterial communities. We concluded that the microbial communities in the Sand Fynbos are highly diverse and closely linked to the above‐ground floral communities.

In vitro bulblet production of Lachenalia - M. M. Slabbert; J. G. Niederwieser (Plant Cell Reports, 1999)